Globalization and the Privatization of Welfare Administration in Indiana - Aman Jr., Alfred C. (Indiana Journal of Global Legal Studies, 2013)
This article explores the relationship of globalization to domestic law in the context of privatized welfare services in Indiana. It examines the ways that privatization can affect vulnerable populations such as welfare recipients by, in effect, partially dis-embedding the market from the state. It applies Karl Polanyi's conception of a double movement to illustrate how the political process can, in effect, re-embed the market in the state. Utilizing Indiana's recent experiences with welfare administration privatization, this article shows that re-embedding is not a simple question of reversing decisions already taken, but rather a complex sequencing of political and legal engagements. It recommends law reforms aimed at more easily triggering the kinds of political actions anticipated by Polanyi's analysis.
Law; Legal Studies
Keywords: GLOBALIZATION; INDIANA; Indiana; POLANYI; Karl; 1886-1964; POLITICAL participation laws; PRIVATIZATION; Public welfare; double movement; global legal studies; globalization; political participation laws; privatization; public welfare